The Modeling and Analysis of Fuel Metering System of Gas Turbine based on AMESim. Issue 1 (1st December 2022) - He, Fengshuo; Ning, Ding; Yong, Lu
Abstract : The fuel metering system is an essential component of gas turbine and an in-depth research on its characteristics is the basis for the design and optimization of the gas turbine fuel system. This paper presents a mathematical modeling analysis of the main components of the fuel metering system and uses AMESim to build a numerical model for computer simulation. The model is used to verify and analyze important performance indicators such as differential pressure and fuel metering response, and to propose key points for optimization in the fuel metering system.